Toxicity of the therapeutic potassium permanganate to tilapia Oreochromis niloticus and to non-target organisms Ceriodaphnia dubia (microcrustacean cladocera) and Pseudokirchneriella subcapitata (green microalgae) - Franca, Jakeline G. [UNESP]; Paiva, Maria J. T. R.; Carvalho, Solange [UNESP]; Miashiro, Luciana; Lombardi, Julio V. (Elsevier B.V., 2011)
Potassium permanganate is a chemical compound widely used in aquaculture for the control and removal of parasites, and in the prevention of diseases caused by bacteria and fungi. However, this compound can be toxic to fish, being a strong oxidant. Moreover, there is no consistent information in the literature about its toxicity to non-target organisms. The purpose of this study was to evaluate the acute toxicity (LC50;96h) of potassium permanganate for tilapia, Oreochromis niloticus, and to determine its toxic effects on nontarget organisms using ecotoxicological assays performed with the microcrustacean Ceriodaphnia dubia and with the green microalgae Pseudokirchneriella subcapitata. The results showed that the concentration of 1.81 mg L-1 of potassium permanganate caused acute toxic effect in tilapia fingerlings. The ecotoxicological assays demonstrated that concentrations above 0.12 mg L-1 can cause chronic toxic effects on non-target organisms, indicating possible deleterious effects on the food chain of the aquatic ecosystem that may receive the discharge of effluents released by fish cultures treated with this chemotherapy. All toxic concentrations determined in this study were below those recommended in the literature for the use of this chemotherapy in fish cultures, demonstrating that this type of therapy should be more carefully considered in order to avoid damage to the treated fish and to the environment. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Potassium permanganate; Ecotoxicity; Oreochromis niloticus; Ceriodaphnia dubia; Pseudokirchneriella subcapitata